A scoping review to inform the development of dementia care competencies. (July 2023) - Kay, Kelly; Metersky, Kateryna; Smye, Victoria; McGrath, Colleen; Johnson, Karen; Astell, Arlene; Sun, Winnie; Bartfay, Emma
Health professionals and care partners of persons living with dementia have expressed that learning needs related to dementia care are a priority. There are currently a variety of training programs available in Ontario (Canada) to address aspects of dementia care, but no commonly accepted description of the core knowledge, skills, and abilities, (i.e., competencies) that should underpin dementia-related training and education in the province. The aim of this study was to review current evidence to inform the later development of competency statements describing the knowledge, skills and actions required for dementia care among care providers ranging from laypersons to health professionals. We also sought to validate existing dementia care principles and align new concepts to provide a useful organizing framework for future competency development. We distinguished between micro-, meso- and macro-level concepts to clarify the competencies required by individuals situated in different locations across the healthcare system, linking competency development in dementia care to broader system transformation. This review precedes the co-development of a holistic competency framework to guide approaches to dementia care training in Ontario.